Europe and the end of Pax Americana: Transatlantic relations must be put on a new footing, regardless of who wins the US elections - Marco Overhaus (Stiftung Wissenschaft und Politik (SWP), 2024)
The idea that US power underpins international security remains deeply anchored in today's US political elite. Ultimately, this idea also lies at the heart of US-led alliances, including NATO. But the three pillars of Pax Americana - US military strength, the country's economic openness and the liberal-democratic foundations of American foreign policy - have, in fact, been crumbling for some time. The outcome of the US elections on 5 November 2024 may accelerate or deaccelerate these trends, but it will not fundamentally reverse them. Against this backdrop, Germany and the other allies will have to ensure that transatlantic relations are put on a new footing after the elections. And this is regardless of whether Kamala Harris or Donald Trump wins the ballot.
Keywords: 320; Pax Americana; US Elections; NATO; Donald Trump; Kamala Harris; international security; liberal-democratic values; Russia; Ukraine; China; Taiwan Strait; military power; economic power; Middle East; geoeconomic thinking; G7 countries; European Union; foreign policy; transatlantic relations; Indo-Pacific